Sobol method for sensitivity analysis of the hydrus model in the simulation of water infiltration in alluvial deposit in the brazilian semiariid - Maria Eduarda Rodrigues da Silva; Severino Martins dos Santos Neto; Rodrigo Lustosa Peronico; Lucas Ravellys Pyrrho de Alcântara; Ialy Rayane de Aguiar Costa; Antonio Celso Dantas Antonino; Artur Paiva Coutinho (Revista Brasileira de Recursos Hídricos, 2024)
ABSTRACT Simulation of water flow in the soil in semiarid regions is fundamental for managing scarce water resources. Aiming for more accurate results, the sensitivity analysis (SA) of the hydrodynamic parameters involved in the simulations is very relevant. This study aims to evaluate the influence of hydrodynamic parameters on the hydrological response of an alluvial deposit in the dry bed of the Capibaribe River using the Hydrus-1D. A global sensitivity analysis method proposed by Sobol was chosen to evaluate the sensitivity of the soil water infiltration curve. A convergence analysis was carried out to investigate the evolution of the indices with increasing sample size. Values of the sensitivity indices showed gross variations at the beginning of the simulations for the different parameters, but they converged within the set of 10,000 samples. For parameters whose sensitivity indices are closer to 0, it is noted that 1,000 samples (14,000 simulations) were sufficient for the index to converge to their final value. The total and first-order sensitivity index calculated with 10,000 samples present the parameters n and Ks as the most important, being expressly more influential than the others.